Migration in South Africa: tensions and post-apartheid inter-ethnic compromises in a central district of Johannesburg - (:unkn) unknown (My University, 2012)
This chapter is set against the backdrop of the multiple forms of violence committed against foreigners in South African cities that underwent a sudden systematisation in townships and informal camps in 2008. The chapter focuses specifically on the increasing demographic diversity of a central district of Johannesburg, formerly a white preserve. The recent urban compromise reached between the local authorities, foreign Africans and native South Africans originally from rural areas and the old Bantustans has proved fragile. The compromise governing urban coexistence has been frequently challenged by discourses and practices positing the radical alterity of foreign migrants. While for some migrants there is significant evidence of inclusion, other migrants have been treated less favorably. Such treatment may involve never gaining recognition as an immigrant, forever remaining at the threshold, waiting indefinitely for a passage to the West, being subject to escheat or being forced to return to the country of origin.
Keywords: African Research